An investigation into the need for environmental information in South Africa: a case study of the Enviro Facts Project - Paxton, Linda Janet (Rhodes University, Faculty of Education, Department of Education, 1994)
Growing awareness of the environmental risks associated with modernity has contributed to an increasing demand for information about the environment. Conservation and other environmental organisations receive many such requests for information. The research reported here was motivated first, by the view that these requests presented an opportunity for environmental education, and second, by a concern that this potential was not being realised. The research question was thus "How can environmental education be supported by optimally responding to requests for environmental information?" It is argued that social change is the raison d' etre of environmental education as a response to environmental risks. Further, it is proposed that this might be best achieved through an approach described here as socially critical environmental education. The study comprised an historical review of the Enviro Facts Project, a recent attempt to meet the need for environmental information; a questionnaire survey; interviews; and workshops. Results were collected from 115 questionnaire responses; 23 telephone interviews and nine face-to-face interviews; and six workshops. The research design was participative. It aimed to answer the research question through co-developing practical solutions with participants. Further, it endeavoured to be of practical relevance to those participants. Conclusions are drawn as to how the research question might be answered. Recommendations are made as follows. Responses to environmental information requests might best support socially critical environmental education through an approach characterised by: * a recognition of the importance of responding optimally to environmental information requests, as well as a recognition of existing structures and resource materials with which to respond; * the mobilisation of those structures and resource materials through, for example, the effective marketing and distribution of resource materials; informed and focused networking to make existing resources and capacities more accessible; and the effective use of libraries to provide environmental information; * the enhancement of the capacities of local sources of environmental information. The findings of this study could usefully inform both resource development in environmental education, and those who in their line of work respond to requests for environmental information.
Keywords: Enviro facts project; Environmental education -- South Africa